Comparative study between the reaction times of collegiate level ranked Valorant players - Dominguez, Job Andrew C. 2001-; Manalo, Jeriel L. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Valorant is a First Person Shooter (FPS) game that is competitive and popular within the Philippines. This is a game that requires in depth game knowledge, equipment, and skills such as reaction time. In this study, the reaction time data of 37 ranked College level Valorant players within Metro Manila were collected and analyzed to find correlation between rank and reaction time and comparison of reaction time between ranks. The Human Benchmark Website and its reaction time test was used to accurately measure the reaction time of the participants. It was found that there was no significant difference between the reaction times of “Low” vs “Medium” ranked Valorant players, while there was a significant difference between “High” ranked players vs “Low” and "Medium” ranked players. It was also found that there is a weak positive correlation between rank and reaction time of these Valorant players. These results show that Higher ranked players tend to have shorter reaction times, meaning that reaction time may be a factor in improving game performance in ranked Valorant
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Pagination different on ecopy
Keywords: eSports players; Reaction time